A Blockchain-Based Cross-Domain Authentication Scheme for Unmanned Aerial Vehicle-Assisted Vehicular Networks - Wenming Wang; Shumin Zhang; Guijiang Liu; Yue Zhao (World Electric Vehicle Journal)
With the rapid increase in the number of vehicles and the growing demand for low-latency and reliable communication, traditional vehicular network architectures face numerous challenges. Unmanned Aerial Vehicle (UAV)-assisted vehicular networks provide an innovative solution for real-time data transmission and efficient cross-domain communication, significantly enhancing resource allocation efficiency and traffic safety. However, these networks also raise privacy and security concerns. Traditional symmetric key and Public Key Infrastructure (PKI)-based authentication schemes suffer from issues such as key management, certificate verification, and data leakage risks. While blockchain technology has been explored to address these problems, it still suffers from inefficiencies and high computational overhead. This paper proposes a UAV-assisted vehicular network architecture that leverages UAVs as trusted intermediaries for cross-domain authentication, effectively reducing authentication delays and improving scalability. Through ProVerif security proofs and detailed theoretical analysis, the proposed scheme is demonstrated to meet the security requirements of vehicular networks and withstand a broader range of attacks. Performance evaluation results show that the proposed scheme achieves at least a 20% reduction in computational and communication overhead compared to existing schemes, highlighting its significant advantages. Additionally, the average consensus time for the proposed scheme is at least 40% lower than existing schemes. The novelty of the proposed scheme lies in the integration of UAVs as trusted intermediaries with blockchain technology, addressing key management and privacy issues, and providing an efficient and secure solution for high-density vehicular networks.